Low-water-absorptivity aramid fiber lithium battery diaphragm, preparation method thereof and lithium ion battery
By preparing fluorinated side-chain aramid polymers to reduce the water absorption and hydrophilicity of aramid membranes, the problem of excessive moisture in aramid membranes was solved, achieving high thermal stability and excellent battery performance.
Patent Information
- Application Number
- CN202511316341.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2025-12-12
Smart Images

Figure CN121123565A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery separator technology, specifically to a low-water-absorption aramid lithium battery separator, its preparation method, and a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries typically consist of a positive electrode, a negative electrode, a separator, and an electrolyte. The main function of the separator is to separate the positive and negative electrodes, preventing short circuits caused by contact between them. It also allows electrolyte ions to pass through. As one of the internal components of a lithium-ion battery, the performance of the separator determines the battery's interface structure, internal resistance, and other characteristics, directly affecting the battery's capacity, cycle life, and safety performance. A high-performance separator plays a crucial role in improving the overall performance of the battery.
[0003] Currently, most separator products on the market consist of a polyethylene substrate coated with a water-based coating containing inorganic particles to form an inorganic ceramic-coated separator. However, this type of separator has a poor electrolyte wetting rate, limiting the battery's electrolyte filling efficiency. Compared to inorganic ceramic-coated separators, existing oil-based PVDF-coated separators have a higher liquid absorption rate, but the PVDF layer is prone to shrinkage at high temperatures and swells in the electrolyte.
[0004] Aramid separators, due to their good liquid absorption rate, low swelling performance, and high heat resistance, hold promise for further applications in lithium-ion batteries. However, aramid fibers contain amide bonds, exhibiting strong polarity and readily forming hydrogen bonds with water molecules. This leads to excessive water content in aramid separators, and the hydrogen-bonded water is difficult to remove through physical heating and baking. Since the moisture content of separators in battery applications must be strictly controlled, generally below 1000 ppm, excessive moisture can cause electrolyte decomposition, generating hydrofluoric acid. Hydrofluoric acid is a highly corrosive acid that severely damages the positive and negative electrode materials and current collectors of lithium batteries, consequently affecting the initial charge / discharge capacity, internal resistance, and cycle life of the battery. Therefore, the hydrophilicity of aramid fibers limits their further application in lithium-ion battery separators. Summary of the Invention
[0005] In view of this, the purpose of this invention is to provide a low-water-absorption aramid lithium battery separator, its preparation method, and a lithium-ion battery thereof. The low-water-absorption aramid lithium battery separator provided by this invention has extremely low moisture content and high thermal stability, and the lithium-ion battery prepared from it exhibits excellent capacity and cycle stability.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a low-water-absorption aramid lithium battery separator, the film-forming raw material of which includes a fluorinated side-chain aramid polymer, wherein the fluorinated side-chain aramid polymer is obtained by polycondensation reaction of a fluorinated side-chain aromatic diamine and an aromatic dicarboxylic acid chloride; The fluorinated side-chain aromatic diamine has the structure shown in Formula 1 or Formula 2: Formula 1; Formula 2; In Equation 1, R is -OCH2(CF2). n X, n=3~10, X is F or H; In Equation 2, R f -O(CF2) m Y or -OCF2CFHOC3F7; the -O(CF2) m In Y, m = 1~4, and Y is F or H.
[0007] Preferably, the preparation method of a fluorinated aromatic diamine having the structure shown in Formula 1 includes the following steps: Under the action of triethylamine, a fluorinated alcohol having the structure shown in formula a undergoes an etherification reaction with 2,4-dinitrofluorobenzene to obtain a fluorinated dinitro compound having the structure shown in formula b. Formula a; Formula b; Under the action of a reducing agent, a fluorinated dinitro compound having the structure shown in Formula b undergoes a reduction reaction to obtain a fluorinated aromatic diamine with the structure shown in Formula 1.
[0008] Preferably, the preparation method of a fluorinated aromatic diamine having the structure shown in Formula 2 includes the following steps: Under the action of a reducing agent, 3-(fluoroalkoxy)nitrobenzene with the structure shown in formula c undergoes a reduction reaction to obtain a hydrazine derivative with the structure shown in formula d. Formula c; Formula d; Under the action of stannous chloride, hydrazine derivatives with the structure shown in formula d undergo acid-catalyzed rearrangement to obtain fluorinated aromatic diamines with the structure shown in formula 2.
[0009] Preferably, the aromatic dicarboxylic chloride is isophthaloyl chloride and / or terephthaloyl chloride; The molar ratio of the fluorinated side-chain aromatic diamine to the aromatic dicarboxylic acid chloride is 1:(1~1.05). The intrinsic viscosity of the fluorinated side-chain aramid polymer is 1.6~3.5 dL / g.
[0010] Preferably, the fluorinated side-chain aramid polymer has the structure shown in Formula 3 or Formula 4: Formula 3; Equation 4; In equations 3 and 4, Z is or ; n = 200~400.
[0011] This invention provides a method for preparing the above-mentioned low-water-absorption aramid lithium battery separator, comprising the following steps: A fluorinated side-chain aromatic diamine and aromatic dicarboxylic acid chloride are mixed with an organic solvent to carry out a polycondensation reaction. A neutralizing agent is added to the resulting polycondensation reaction solution to obtain a fluorinated side-chain aramid polymer slurry. The fluorinated side-chain aramid polymer slurry is mixed with a pore-forming agent to obtain a casting solution; The casting liquid is extruded onto the substrate surface to form a liquid film. The liquid film is then subjected to coagulation bath film formation, stretching, solvent removal, drying, and heat setting in sequence to obtain a low water absorption aramid lithium battery separator.
[0012] Preferably, the neutralizing agent includes one or more of calcium hydroxide, potassium hydroxide, and sodium hydroxide; The solid content of the fluorinated side-chain aramid polymer slurry is 10-30%.
[0013] Preferably, the pore-forming agent includes one or more of calcium chloride, lithium chloride, polyvinylpyrrolidone, and polyethylene glycol; The mass of the pore-forming agent is 2-10% of the mass of the fluorinated side-chain aramid polymer slurry; The rotational viscosity of the casting solution is 150~900 Pa·s.
[0014] Preferably, the coagulation bath comprises a first component and a second component; The first component includes water, or a combination of water and an alcohol solvent; The second component includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and triethyl phosphate; The mass ratio of the first component to the second component in the coagulation bath is (20~45):(55~80); The film-forming temperature in the coagulation bath is 10~40℃, and the time is 30~250s.
[0015] This invention provides the application of the above-mentioned low water absorption aramid lithium battery separator in lithium-ion batteries.
[0016] The present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the separator is the aforementioned low-water-absorption aramid lithium battery separator.
[0017] This invention provides a low-water-absorption aramid lithium battery separator. The film-forming raw material includes a fluorinated side-chain aramid polymer, which is obtained by polycondensation reaction of a fluorinated side-chain aromatic diamine and an aromatic dicarboxylic acid chloride. The fluorinated side-chain aromatic diamine has the structure shown in Formula 1 or Formula 2. Fluorine is the most electronegative element, with a very small van der Waals radius and low polarizability, resulting in a high bond energy for carbon-fluorine covalent bonds, reaching 490 kJ / mol. Unique secondary interactions exist between the fluorinated segments of the polymer. The low surface energy of the fluorinated side chains causes the fluorinated side chains to partially encapsulate the hydrophilic amide groups on the aramid backbone, creating a shielding effect on the carbon chain, reducing the surface energy of the material, decreasing the contact between the material and water molecules, thereby improving the stability and hydrophobicity of the polymer material. However, the number of polyamides with hydrogen atoms on the aromatic ring replaced by fluorine is limited. Besides the difficulty in synthesizing the monomers, another important reason is that the reactivity of the diamine is significantly reduced due to fluorine substitution. Therefore, only a few polymers can achieve a sufficiently high relative molecular mass, while others struggle to reach the molecular mass required for film formation. This invention utilizes a specific, highly reactive fluorinated aromatic diamine. Through the condensation reaction of aromatic dicarboxylic acid chloride with the fluorinated aromatic diamine, the fluorinated side chain is introduced into the aramid membrane. This causes the electron cloud to shift towards the fluorine atom, reducing the electron density of the benzene ring and weakening its ability to form hydrogen bonds with water molecules. Simultaneously, the hydrophobicity of the fluorinated side chain counteracts the polarity of the amide bond (-NH-CO-), reducing the overall molecular polarity. The steric hindrance of the fluorinated side chain can partially encapsulate the hydrophilic amide groups on the aramid backbone, reducing their contact with water molecules. This invention significantly reduces the water absorption rate and affinity for water in aramid separators by controlling the chain length of the perfluorinated chain to increase the fluorine content. Vacuum baking allows for control of the separator's water content within commercially acceptable limits. Furthermore, the low-water-absorption aramid lithium-ion battery separator provided by this invention combines the low swelling and high heat resistance of aramid polymers, resulting in lithium-ion batteries with excellent capacity, cycle stability, and safety performance. Example results show that the low-water-absorption aramid lithium-ion battery separator provided by this invention has a water content of 205.4~685.6 ppm and a glass transition temperature of 228~293℃, and the resulting lithium-ion batteries exhibit high cycle stability and high capacity retention.
[0018] This invention provides a method for preparing the above-mentioned low water absorption aramid lithium battery separator. This method is simple to operate, low in cost, and easy to achieve industrial mass production. Attached Figure Description
[0019] Figure 1 The electrical performance of lithium-ion batteries assembled with the separators obtained in Examples 1, 5, and Comparative Examples 1-3 is shown. Detailed Implementation
[0020] This invention provides a low-water-absorption aramid lithium battery separator, the film-forming raw material of which includes a fluorinated side-chain aramid polymer, wherein the fluorinated side-chain aramid polymer is obtained by polycondensation reaction of a fluorinated side-chain aromatic diamine and an aromatic dicarboxylic acid chloride; The fluorinated side-chain aromatic diamine has the structure shown in Formula 1 or Formula 2: Formula 1; Formula 2; In Equation 1, R is -OCH2(CF2). n X, n=3~10, X is F or H; preferably, n=3, X is F; or n=6, X is F; or n=7, X is F; or n=10, X is H.
[0021] In Equation 2, R f -O(CF2) m Y or -OCF2CFHOC3F7; the -O(CF2) m In Y, m = 1~4, preferably m = 1~2; Y is F or H, specifically -OCF3 or -OCF2CF2H.
[0022] In this invention, the method for preparing a fluorinated aromatic diamine with a side chain having the structure shown in Formula 1 preferably includes the following steps: Under the action of triethylamine, a fluorinated alcohol having the structure shown in formula a undergoes an etherification reaction with 2,4-dinitrofluorobenzene to obtain a fluorinated dinitro compound having the structure shown in formula b. Formula a; Formula b; Under the action of a reducing agent, a fluorinated dinitro compound having the structure shown in Formula b undergoes a reduction reaction to obtain a fluorinated aromatic diamine with the structure shown in Formula 1.
[0023] In this invention, under the action of triethylamine, a fluorinated alcohol having the structure shown in formula a undergoes an etherification reaction with 2,4-dinitrofluorobenzene to obtain a fluorinated dinitro compound having the structure shown in formula b. In this invention, the fluorinated alcohol having the structure shown in formula a is preferably F(CF2)3CH2OH (heptafluorobutanol), F(CF2)6CH2OH (tetrazol), F(CF2)7CH2OH (pentadecylfluorooctanol), or H(CF2). 10 CH2OH (eicofluoroundecyl alcohol).
[0024] In this invention, the molar ratio of the fluorinated alcohol having the structure shown in Formula a to 2,4-dinitrofluorobenzene is preferably 1:1, and the molar ratio of the fluorinated alcohol having the structure shown in Formula a to triethylamine is preferably 1:(1.1~1.5), more preferably 1:(1.2~1.4). In this invention, the reaction solvent for the etherification reaction is preferably one or more of N,N-dimethylacetamide, DMF, DMSO, acetone, and acetonitrile. In this invention, the temperature of the etherification reaction is preferably room temperature, more preferably 25°C, and the time is preferably 2~4 hours, more preferably 3 hours. After the etherification reaction, this invention preferably involves adding water to precipitate the obtained etherification reaction product, followed by filtration and drying to obtain a fluorinated dinitro compound having the structure shown in Formula b.
[0025] In this invention, under the action of a reducing agent, a fluorinated dinitro compound having the structure shown in Formula b undergoes a reduction reaction to obtain a fluorinated aromatic diamine with a side chain having the structure shown in Formula 1. In this invention, the reducing agent preferably includes one or more of stannous chloride, H2, iron powder, zinc powder, ammonium formate, sodium sulfide, and sodium bisulfite, more preferably stannous chloride; the molar ratio of the reducing agent to the fluorinated dinitro compound having the structure shown in Formula b is preferably (6~18):1, more preferably (10~15):1.
[0026] In this invention, when the reducing agent is stannous chloride, the reduction reaction is preferably carried out in a hydrochloric acid and acetic acid solution environment. The mass concentration of the hydrochloric acid is preferably 36%, the purity of the acetic acid is preferably ≥99.5%, and the molar ratio of hydrochloric acid to acetic acid is preferably (2~3):1. In this invention, the temperature of the reduction reaction is preferably 80~100℃, more preferably 90℃, and the time is preferably 4~6h, more preferably 5h. By carrying out the reduction reaction in an acidic environment, this invention provides protonated hydrogen, allowing stannous chloride, as a reducing agent, to provide electrons, promoting the reduction of dinitrobenzene to phenylenediamine. Furthermore, the acidic environment prevents tin salt precipitation and ensures the normal progress of the reduction reaction. Because water is produced during the reduction process, stannous chloride reacts with water to form insoluble basic salts, which coat the surface of the stannous chloride, causing it to lose its reducing ability.
[0027] Following the reduction reaction, the present invention preferably performs post-processing on the obtained reduction reaction product, the post-processing preferably including the following steps: The product of the reduction reaction was neutralized with alkali solution, and then extracted with organic solvent and the organic solvent was removed to obtain a crude product. The crude product was then sublimated and recrystallized to obtain a pure fluorinated aromatic diamine with the structure shown in Formula 1.
[0028] In this invention, the alkaline solution is preferably a NaOH solution; the organic solvent used for extraction is preferably ethyl acetate, and the method for removing the organic solvent is preferably evaporation; in this invention, the solvent used for recrystallization is preferably a benzene-hexane mixed solvent, and the volume ratio of benzene to hexane in the mixed solvent is preferably 1:(1~4), more preferably 1:3.
[0029] In this invention, the preferred synthetic route for fluorinated aromatic diamines with the structure shown in Formula 1 is as shown in Formula A: Formula A.
[0030] In this invention, the method for preparing a fluorinated aromatic diamine with the structure shown in Formula 2 preferably includes the following steps: Under the action of a reducing agent, 3-(fluoroalkoxy)nitrobenzene with the structure shown in formula c undergoes a reduction reaction to obtain a hydrazine derivative with the structure shown in formula d. Formula c; Formula d; Under the action of stannous chloride, hydrazine derivatives with the structure shown in formula d undergo acid-catalyzed rearrangement to obtain fluorinated aromatic diamines with the structure shown in formula 2.
[0031] In this invention, 3-(fluoroalkoxy)nitrobenzene having the structure shown in formula c undergoes a reduction reaction under the action of a reducing agent to obtain a hydrazine derivative having the structure shown in formula d. In this invention, the method for preparing 3-(fluoroalkoxy)nitrobenzene having the structure shown in formula c preferably includes the following steps: When R f When the molecule is -OCF3, 3-nitrophenol with the structure shown in formula e undergoes a fluorination reaction with carbon tetrachloride and anhydrous hydrogen fluoride under the catalysis of boron trifluoride to obtain 3-(fluoroalkoxy)nitrobenzene with the structure shown in formula c.
[0032] Formula e; In this invention, the molar ratio of boron trifluoride to 3-nitrophenol is preferably (0.15~0.25):1, more preferably 0.2:1; the molar ratio of carbon tetrachloride to 3-nitrophenol is preferably (2~4):1, more preferably 3:1; and the molar ratio of anhydrous hydrogen fluoride to 3-nitrophenol is preferably (15~25):1, more preferably 20:1.
[0033] In this invention, the temperature of the fluorination reaction is preferably 120~140℃, more preferably 130℃; the time is preferably 10~16h, more preferably 12~14h.
[0034] When R fWhen the form is -OCF2CF2H, 3-(fluoroalkoxy)nitrobenzene with the structure shown in formula c is 3-(1,1,2,2-tetrafluoroethoxy)nitrobenzene, which can be purchased commercially.
[0035] When R f When the structure is -OCF2CFHOC3F7, in the presence of an organic base, 3-nitrophenol having the structure shown in formula e undergoes a base-catalyzed addition reaction with perfluoropropyl vinyl ether to obtain a compound having the structure shown in formula c. In this invention, the organic base is preferably potassium tert-butoxide, and the molar ratio of perfluoropropyl vinyl ether to 3-nitrophenol is preferably (1~1.2):1, and the molar ratio of 3-nitrophenol to potassium tert-butoxide is preferably (15~20):1. In this invention, the organic solvent used in the base-catalyzed addition reaction is preferably N,N-dimethylformamide; the temperature of the base-catalyzed addition reaction is preferably 20~30°C, and the time is preferably 12~16 h.
[0036] In this invention, the synthetic route for the 3-(fluoroalkoxy)nitrobenzene having the structure shown in Formula c is preferably as shown in Formula B: Formula B; In equation B, Z = F or OC3F7.
[0037] In this invention, 3-(fluoroalkoxy)nitrobenzene having the structure shown in formula c undergoes a reduction reaction under the action of a reducing agent to obtain a hydrazine derivative having the structure shown in formula d. In this invention, the reducing agent is preferably sodium borohydride, and the molar ratio of 3-(fluoroalkoxy)nitrobenzene having the structure shown in formula c to sodium borohydride is preferably 1:(2~4), more preferably 1:(2.5~3.5); the organic solvent used in the reduction reaction is preferably dimethyl sulfoxide. In this invention, the temperature of the reduction reaction is preferably 100~110℃, more preferably 105℃, and the time is preferably 4~8 min, more preferably 5 min.
[0038] In this invention, a hydrazine derivative having the structure shown in Formula d undergoes an acid-catalyzed rearrangement reaction under the action of stannous chloride to obtain a fluorinated aromatic diamine with the structure shown in Formula 2. In this invention, the molar ratio of the fluorinated aromatic diamine with the structure shown in Formula 2 to stannous chloride is preferably (0.4~2.5):1, more preferably (1~2):1; the acid-catalyzed rearrangement reaction is preferably carried out in the presence of concentrated hydrochloric acid. In this invention, the temperature of the acid-catalyzed rearrangement reaction is preferably 20~30°C, and the time is preferably 12~16 h.
[0039] In this invention, the preferred synthetic route for fluorinated aromatic diamines with the structure shown in Formula 2 is as shown in Formula C: Formula C.
[0040] In this invention, when R f When the fluorinated side-chain aromatic diamine is -OCF3, the fluorinated side-chain aromatic diamine with the structure shown in Formula 2 is 2,2'-bis(trifluoromethoxy)-biphenyldiamine, which can be purchased commercially.
[0041] In this invention, the aromatic dicarboxylic chloride is preferably isophthaloyl chloride and / or terephthaloyl chloride; the molar ratio of the fluorinated side-chain aromatic diamine and the aromatic dicarboxylic chloride is preferably 1:(1~1.05), more preferably 1:1.
[0042] In this invention, the intrinsic viscosity of the fluorinated side-chain aramid polymer is preferably 1.6~3.5 dL / g, more preferably 2~3 dL / g.
[0043] In this invention, the fluorinated side-chain aramid polymer has the structure shown in Formula 3 or Formula 4: Formula 3; Equation 4; In equations 3 and 4, Z is or ; n = 200~400, specifically 200, 250, 300, 350 or 400.
[0044] In this invention, the thickness of the low water absorption aramid lithium battery separator is preferably 10~16μm, more preferably 14μm, the pore size is preferably 0.04~0.2μm, more preferably 0.08~0.15μm, and even more preferably 0.1~0.12μm; the porosity is preferably 40~70%, more preferably 50~60%.
[0045] This invention provides a method for preparing the above-mentioned low-water-absorption aramid lithium battery separator, comprising the following steps: A fluorinated side-chain aromatic diamine and aromatic dicarboxylic acid chloride are mixed with an organic solvent to carry out a polycondensation reaction. A neutralizing agent is added to the resulting polycondensation reaction solution to obtain a fluorinated side-chain aramid polymer slurry. The fluorinated side-chain aramid polymer slurry is mixed with a pore-forming agent to obtain a casting solution; The casting liquid is extruded onto the substrate surface to form a liquid film. The liquid film is then subjected to coagulation bath film formation, stretching, solvent removal, drying, and heat setting in sequence to obtain a low water absorption aramid lithium battery separator.
[0046] This invention involves mixing a fluorinated side-chain aromatic diamine, an aromatic dicarboxylate chloride, and an organic solvent to perform a polycondensation reaction. A neutralizing agent is then added to the resulting polycondensation reaction solution to obtain a fluorinated side-chain aramid polymer slurry. In this invention, the organic solvent preferably includes one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), and triethyl phosphate (TEP). In this invention, the aromatic dicarboxylate chloride is preferably isophthaloyl chloride and / or terephthaloyl chloride; the molar ratio of the fluorinated side-chain aromatic diamine to the aromatic dicarboxylate chloride is preferably 1:(1~1.05), more preferably 1:1. In this invention, the temperature of the polycondensation reaction is preferably -25~-5℃, more preferably -15℃, and the time is preferably 2~10h, more preferably 4~6h.
[0047] In this invention, the neutralizing agent preferably includes one or more of calcium hydroxide, potassium hydroxide, and sodium hydroxide. When the neutralizing agent is calcium hydroxide, the molar ratio of the fluorinated side-chain aromatic diamine to the neutralizing agent is preferably 1:(1.05~1.1). When the neutralizing agent is potassium hydroxide or sodium hydroxide, the molar ratio of the fluorinated side-chain aromatic diamine to the neutralizing agent is preferably 1:(2.1~2.2). In this invention, the solid content of the fluorinated side-chain aramid polymer slurry is preferably 10~30%, more preferably 15~25%, and even more preferably 17~20%.
[0048] After obtaining the fluorinated side-chain aramid polymer slurry, the present invention mixes the fluorinated side-chain aramid polymer slurry with a pore-forming agent to obtain a casting solution. In the present invention, the pore-forming agent includes one or more of calcium chloride, lithium chloride, polyvinylpyrrolidone, and polyethylene glycol. Preferably, the molecular weight of the polyvinylpyrrolidone is 30,000 to 60,000, and the molecular weight of the polyethylene glycol is preferably 400 to 20,000. Preferably, the mass of the pore-forming agent is 2 to 10% of the mass of the fluorinated side-chain aramid polymer slurry, more preferably 5 to 8%, specifically 2%, 4%, 5%, 6%, 8%, or 10%. In this invention, the rotational viscosity of the casting solution is 150~900 Pa·s, more preferably 400~600 Pa·s, specifically 150 Pa·s, 200 Pa·s, 300 Pa·s, 400 Pa·s, 500 Pa·s, 600 Pa·s, 700 Pa·s, 800 Pa·s or 900 Pa·s.
[0049] After obtaining the casting solution, the casting solution of the present invention is extruded onto the surface of the substrate to form a liquid film. The liquid film is then subjected to coagulation bath film formation, stretching, solvent removal, drying, and heat setting in sequence to obtain a low-water-absorption aramid lithium battery separator. In the present invention, the substrate is preferably a tetrafluoroethylene chain. The present invention does not have special requirements on the length and width of the substrate; it can be designed according to actual needs. In the present invention, the thickness of the liquid film is preferably 10~15μm, more preferably 11~13μm.
[0050] In this invention, the coagulation bath preferably comprises a first component and a second component; the first component preferably comprises water, or a combination of water and an alcohol solvent, more preferably water; in this invention, the alcohol solvent is preferably one or more of ethanol, propanol, and isopropanol, and when the first component is a combination of water and an alcohol solvent, the mass ratio of water to alcohol solvent is preferably (70~100):(0~30). In this invention, the second component comprises one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and triethyl phosphate. In this invention, the mass ratio of the first component to the second component in the coagulation bath is preferably (20~45):(55~80), more preferably (25~40):(60~75), specifically 20:80, 25:75, 30:70, 40:60, or 45:55. This invention, by controlling the composition of the coagulation bath and the mass ratio of the first and second components, can control the pore size and porosity of the separator, and adjust the gelation rate of the liquid membrane to match the production process. Specifically, when the content of the first component is too high, the gelation rate of the liquid membrane is too fast, forming macroporous polymers, and the number of pores on the entire membrane surface is low. This makes it unsuitable for use as a lithium battery separator, both in terms of poor membrane strength and lithium ion transport within the membrane. When the content of the first component is too low, the gelation rate is too slow, the matrix cannot achieve the transfer process of the liquid membrane, and it is difficult to form.
[0051] In this invention, the temperature of the coagulation bath for film formation is 10~40℃, more preferably 20~30℃, and the time is preferably 30~250s, more preferably 60~180s, specifically 30s, 60s, 90s, 120s, 150s, 180s, 220s or 250s.
[0052] The present invention preferably uses a horizontal stretching machine to perform the stretching; in the present invention, the stretching ratio is preferably 1 to 3 times, specifically 1, 2 or 3 times.
[0053] In this invention, the solvent removal method is preferably extraction; the extractant used in the extraction is preferably water, and the temperature of the extractant is preferably 50-80°C, more preferably 60-70°C. This invention, through extraction solvent removal, can form a porous membrane.
[0054] In this invention, the drying is preferably hot air drying and / or infrared drying, and the drying temperature is preferably 70~150℃, more preferably 100~120℃.
[0055] In this invention, the heat setting is preferably hot air setting and / or infrared heating heat setting, the heat setting temperature is preferably 150~300℃, more preferably 200~250℃, and the heat setting time is preferably 30~300s, more preferably 100~200s. After heat setting, the invention preferably performs a winding process.
[0056] In this invention, the low-water-absorption aramid lithium battery separator is preferably vacuum-baked before moisture content testing or actual use to control its moisture content. The vacuum baking process preferably comprises three sequential stages: the first stage includes baking under vacuum at 140-160°C, preferably 150°C, for 15-20 hours; the second stage includes purging with nitrogen to a pressure of 0.1-0.6 MPa and holding the pressure for 15-25 minutes; and the third stage includes baking under vacuum at 120-140°C, preferably 130°C, for 15-16 hours. This invention, through nitrogen pressure holding, disrupts the moisture adsorption balance in the separator, further reducing its moisture content.
[0057] This invention provides the application of the above-mentioned low water absorption aramid lithium battery separator in lithium-ion batteries.
[0058] This invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the separator is the aforementioned low-water-absorption aramid lithium battery separator. This invention does not have specific requirements regarding the types of the positive electrode, negative electrode, and electrolyte; commonly known in the field of lithium-ion batteries can be used. As a specific embodiment of this invention, the positive electrode comprises a ternary positive electrode material (LiMn). 0.1 Co 0.1 Ni 0.8 The negative electrode comprises graphite, conductive carbon black, styrene-butadiene rubber, and binder (CMC) in a mass ratio of 97:2:1. The electrolyte solvent consists of DMC, EC, and DEC in a volume ratio of 1:1:1. The electrolyte is LiPF6 lithium salt with a concentration of 1 mol / L.
[0059] The present invention does not have any special requirements for the assembly method of the lithium-ion battery; any assembly method known to those skilled in the art can be used.
[0060] The following detailed description, in conjunction with embodiments, illustrates the low water absorption aramid lithium battery separator, its preparation method, and the lithium-ion battery provided by this invention. However, these descriptions should not be construed as limiting the scope of protection of this invention.
[0061] In the following examples, ① the intrinsic viscosity test method is as follows: using 96% sulfuric acid as solvent, accurately weigh the dried sample to prepare a 0.005 g / mL solution, and test it in a constant temperature water bath at 25°C using a single-point method with an Ubbelohde viscometer. The intrinsic viscosity [η] is calculated using the following formula (1).
[0062] [η] = [2(η】 sp -lnη r )] 0.5 / C formula (1); In equation (1): η sp To increase specific viscosity; η r C represents the relative viscosity; C is the concentration of the sample in the solution, which is 0.005 g / mL.
[0063] ② The rotational viscosity test method is as follows: Take a sample from the sample, ensuring it is completely free of air bubbles, and place it in a constant-temperature measuring container. Adjust the temperature to 25℃±0.1℃, place the coaxial measuring cylinder into the measuring container, turn on the instrument (using a Brookfield HBDV2T series rotational viscometer), and read the indicated value after the pointer stabilizes. Perform several measurements on the same sample, repeating the determination at different shear rates.
[0064] ③ The moisture content was tested using a METTLER TOLEDO C30S coulometric Karl Fischer moisture analyzer. Before testing, the diaphragm was baked in a vacuum oven in three stages. Stage 1: Baking at 150℃ for 20 hours; Stage 2: Pressurizing with nitrogen for 15 minutes to disrupt the moisture adsorption balance; Stage 3: Baking under vacuum for another 15 hours, with the oven temperature set at 130℃.
[0065] ④ Glass transition temperature (T) g The test method is as follows: the glass transition temperature (T) of the fluorinated aramid is determined using DSC (Q2000, Waters China Co., Ltd.). g Under N2 protection, the temperature was increased to 350℃ at a rate of 10℃ / min, held for 5 minutes, cooled to 80℃, and then increased to 350℃ again at the same rate. The curve of the second heating was recorded.
[0066] In Examples 1-4, the fluorinated side-chain aromatic diamines have the structure shown in Formula 1, where R in Formula 1 are: .
[0067] In Examples 5-7, the fluorinated side-chain aromatic diamines have the structure shown in Formula 2, where R in Formula 2... f respectively: .
[0068] ⑤ The electrical performance test method is as follows: under normal temperature conditions, charge at 1C to 4.2V, cut-off current 0.05C; rest for 10 minutes; discharge at 3C to 2.6V; rest for more than 30 minutes until the capacity is ≤80%.
[0069] Example 1 (1) The synthesis of fluorinated side-chain aromatic diamines is carried out using the following steps: 800.0 g (4 mol) heptafluorobutanol, 446.0 g (4.4 mol) triethylamine and 744 g (4 mol) m-dinitrofluorobenzene were stirred in 4000 mL DMAc for 2 h, precipitated in water, filtered and dried to obtain a fluorinated dinitro compound; A mixture of 2700 g stannous chloride, 5940 g 36% hydrochloric acid, 1800 g acetic acid (99.5% purity), and 372 g (2 mol) of a fluorinated dinitro compound was stirred at 25 °C for 2 h, then reacted at 100 °C for 6 h. After cooling to room temperature, the mixture was neutralized with NaOH solution, extracted with ethyl acetate, and then the ethyl acetate was evaporated to obtain the crude product. The product was purified by sublimation and recrystallization in a benzene-hexane mixed solvent (mass ratio 1:3) to obtain a fluorinated aromatic diamine with a side chain of Formula 1, wherein R is OCH2(CF2)3F.
[0070] (2) The preparation of fluorinated side-chain aramid polymer slurry and casting solution adopts the following steps: Under nitrogen protection, 615.95 g (2 mol) of fluorinated side-chain aromatic diamine was dissolved in 5800 mL of DMAC at -15℃. 408.59 g (2 mol) of isophthaloyl chloride was slowly added in portions over 3 hours. After reacting for 2 hours, 156.24 g (2.1 mol) of calcium hydroxide was added to obtain a fluorinated side-chain aramid polymer slurry with a solid content of 17%. 2 wt% (w / w) of polyethylene glycol (a pore-forming agent) was added to the fluorinated side-chain aramid polymer slurry, and the mixture was stirred until homogeneous to obtain a casting solution.
[0071] (3) The preparation of the low water absorption aramid lithium battery separator adopts the following steps: The above casting solution was extruded onto a PTFE chain to form a liquid film. The PTFE chain, along with the liquid film, was immersed in a coagulation bath composed of water and DMAc at a mass ratio of 25:75. The coagulation bath temperature was 28°C, and the film was held in the coagulation bath for 100 seconds, during which the liquid film solidified. The film was then peeled off from the PTFE chain, stretched 1.5 times in a stretching machine, washed with hot water at 55°C, dried at 100°C, and then heat-set at 290°C for 60 seconds to obtain a low-water-absorption aramid lithium battery separator.
[0072] Example 2 The difference from Example 1 is that heptafluorobutanol in step (1) is replaced with tridecafluoroheptanol, and the rest of the operations are the same.
[0073] Example 3 The difference from Example 1 is that heptafluorobutanol in step (1) is replaced with pentadecylfluorooctanol, while the rest of the operations are the same.
[0074] Example 4 The difference from Example 1 is that heptafluorobutanol in step (1) is replaced with eicosicoundecyl alcohol, and the rest of the operations are the same.
[0075] Example 5 (1) The preparation of fluorinated side-chain aramid polymer slurry and casting solution adopts the following steps: Under nitrogen protection, 708.42 g (2 mol) of 2,2'-bis(trifluoromethoxy)-biphenyldiamine was dissolved in 6100 mL of DMAC at -15 °C. 408.59 g (2 mol) of isophthaloyl chloride was slowly added in portions over 3 hours. After reacting for 2 hours, 156.24 g (2.1 mol) of calcium hydroxide was added to obtain a fluorinated side-chain aramid polymer slurry with a solid content of 17%. 2 wt% (w / w) of polyethylene glycol (a pore-forming agent) was added to the fluorinated side-chain aramid polymer slurry, and the mixture was stirred until homogeneous to obtain a casting solution.
[0076] (2) The membrane preparation is as described in step (3) of Example 1.
[0077] Example 6 (1) The synthesis of bis(fluoroalkoxy)benzidine is carried out using the following steps: 1.2 L of DMSO was cooled in an ice bath under nitrogen atmosphere, and 100 g (2.64 mol) of sodium borohydride was slowly added at 18–20 °C. While stirring, 200 g (0.84 mol) of 3-(1,1,2,2-tetrafluoroethoxy)nitrobenzene was added over 0.25 h. The cold bath was removed, and the reactants were allowed to heat to 55 °C due to exothermic reaction. The mixture was heated to 105 °C and held for 5 min, then cooled to room temperature. It was diluted with 1 L of dichloromethane and 1.5 L of water, cooled to 10 °C in an ice bath, and 200 mL of concentrated hydrochloric acid was slowly added. The organic layer was separated, washed with 1 L of water, dried on anhydrous magnesium sulfate, filtered, and concentrated to give 171.8 g of the intermediate compound (the corresponding hydrazine derivative).
[0078] A solution of the intermediate compound in 250 mL of diethyl ether was added dropwise to a mixture of 500 mL concentrated hydrochloric acid, 125 g stannous chloride, 250 mL diethyl ether, and 250 mL dichloromethane, cooled in an ice bath. Another 500 mL of concentrated hydrochloric acid was added, and the mixture was stirred overnight at room temperature. The organic solvent was evaporated from the mixture, and the white solid was filtered off and stirred in 300 mL dichloromethane and 300 mL 10% NaOH. The organic layer was separated, dried on anhydrous magnesium sulfate, and concentrated to give a dark oily substance. The substance was distilled under reduced pressure, and the fraction collected at 180–185 °C / 0.5 mmHg yielded 151.4 g of the oil. NMR analysis determined that approximately 67% of the oil was the target product benzidine, and 33% was an isomer. The mixture was dissolved in 1 L of dichloromethane, saturated with hydrogen chloride, and the precipitate was filtered off. The precipitate was then stirred in diethyl ether and 10% NaOH to convert it into a diamine. The ether solution was dried with magnesium sulfate and concentrated. This process was repeated twice. Then, vacuum distillation was performed, and the solution was taken at 150 °C / 0.2 mmHg to obtain 95.8 g (55%) of 2,2'-bis(1,1,2,2-tetrafluoroethoxy)-4,4'-benzidine.
[0079] (2) The preparation of fluorinated side-chain aramid polymer slurry and casting solution adopts the following steps: Under nitrogen protection, 418.62 g (1 mol) of 2,2'-bis(1,1,2,2-tetrafluoroethoxy)-4,4'-benzidine was dissolved in 3400 mL of DMAC at -15 °C. 204.3 g (1 mol) of isophthaloyl chloride was slowly added in portions over 3 hours. After reacting for 2 hours, 78.12 g (1.05 mol) of calcium hydroxide was added to obtain a fluorinated side-chain aramid polymer slurry with a solid content of 17%. 2 wt% (w / w) of polyethylene glycol (a pore-forming agent) was added to the fluorinated side-chain aramid polymer slurry, and the mixture was stirred until homogeneous to obtain a casting solution.
[0080] (3) The membrane preparation is as in Example 1 (3).
[0081] Example 7 (1) The synthesis of bis(fluoroalkoxy)benzidine is carried out using the following steps: Add 5 g (0.045 mol) potassium tert-butoxide to 106 g (0.76 mol) 3-nitrophenol in 700 mL at 15 °C. In a DMF solution, the mixture was stirred at room temperature for 10 min. 242 g (0.91 mol) of perfluoropropyl vinyl ether was added dropwise over 2 h, the temperature was raised exothermically to 30 °C, and the mixture was stirred overnight. The solution was then poured into 3 L of ice water containing 10 mL of concentrated hydrochloric acid. The aqueous layer was extracted with dichloromethane, and the organic layer was washed with water and dried over anhydrous magnesium sulfate. After concentration, the solution was distilled under reduced pressure at 83–91 °C / 0.5 mmHg to obtain 285 g (93%) of 3-[2-(heptafluoropropoxy)-1,1,2-trifluoroethoxy]nitrobenzene oil.
[0082] 225.7 g (0.557 mol) of 3-[2-(heptafluoropropoxy)-1,1,2-trifluoroethoxy]nitrobenzene was reacted with 66.2 g (1.75 mol) of sodium borohydride in DMSO as in Example 6, yielding 191.1 g of an intermediate compound (the corresponding hydrazine derivative). At -4 °C, a solution of 65.1 g of this product in 75 mL of dichloromethane and 50 mL of diethyl ether was added dropwise to a solution of 400 mL of concentrated hydrochloric acid and 40 g of stannous chloride, followed by the addition of 50 mL of dichloromethane. The mixture was stirred overnight at room temperature. The mixture was concentrated at 35 °C to remove the organic solvent, and the aqueous solution was decanted from the gel. The gel was washed with water, then stirred in 1 L of diethyl ether and 500 mL of 10% KOH solution. The aqueous phase was saturated with ammonium chloride, the ether layer was separated, dried on magnesium sulfate, and concentrated to give 63.15 g of a dark oil. The oily substance was distilled under reduced pressure at 140 °C / 0.3 mmHg to give 6.0 g of 3-[2-(heptafluoropropoxy)-1,1,2-trifluoroethoxy]-aniline. Distillation at 149–163 °C / 0.3 mmHg yielded 53.9 g of product. NMR analysis revealed the main fraction to be a mixture of benzidine isomers. The product was subjected to column chromatography (6 × 34 cm), first eluented with 5.7 L of 5% ethyl acetate in hexane, then with 2.6 L of 10% ethyl acetate in hexane. The 5% ethyl acetate eluent yielded 19.8 g of oily product, identified by NMR as 2,2'-diamino-4,4'-bis[2-(heptafluoropropoxy)-1,1,2-trifluoroethoxybiphenyl]. 15.9 g of the product was obtained from 10% ethyl acetate eluent. The product was then distilled under reduced pressure at 150-160 °C / 0.3 mmHg to obtain the target product 2,2'-bis(2-heptafluoropropoxy)-1,1,2-trifluoroethoxy-4,4'-benzidine.
[0083] (2) The preparation of fluorinated side-chain aramid polymer slurry and casting solution adopts the following steps: Under nitrogen protection, 360.25 g (0.5 mol) of 2,2'-bis(2-heptafluoropropoxy)-1,1,2-trifluoroethoxy-4,4'-benzidine was dissolved in 2500 mL of DMAC at -15 °C. 102.15 g (0.5 mol) of isophthaloyl chloride was slowly added in portions over 3 hours. After reacting for 2 hours, 40.7 g (0.55 mol) of calcium hydroxide was added to obtain a fluorinated side-chain aramid polymer slurry with a solid content of 17%. 2 wt% (w / w) of polyethylene glycol (a pore-forming agent) was added to the fluorinated side-chain aramid polymer slurry, and the mixture was stirred until homogeneous to obtain a casting solution.
[0084] (3) The membrane preparation is as in Example 1 (3).
[0085] Comparative Example 1 The difference from Example 1 is that step (1) is omitted, and the fluorinated side-chain aromatic diamine in step (2) is replaced with m-phenylenediamine. All other operations are the same.
[0086] Comparative Example 2 (1) The preparation of fluorinated side-chain aramid polymer slurry and casting solution adopts the following steps: Under nitrogen protection, 644.48 g (2 mol) of 2,2'-bis(trifluoromethyl)-biphenyldiamine was dissolved in 5800 mL of DMAC at -15 °C. 408.59 g (2 mol) of isophthaloyl chloride was slowly added in portions over 3 hours. After reacting for 2 hours, 156.24 g (2.1 mol) of calcium hydroxide was added to obtain a fluorinated side-chain aramid polymer slurry with a solid content of 17%. 2 wt% (w / w) of polyethylene glycol (a pore-forming agent) was added to the fluorinated side-chain aramid polymer slurry, and the mixture was stirred until homogeneous to obtain a casting solution.
[0087] (2) The membrane preparation is as in Example 1 (3).
[0088] Comparative Example 3 The commercial PE separator used is from Shenzhen Xingyuan Material Technology Co., Ltd., with a thickness of 9+1+3+1 μm.
[0089] Comparative Example 4 The commercial PE separator selected is from Lixiang New Energy Technology Co., Ltd., with a thickness of 9+1+3+1 μm.
[0090] Comparative Example 5 The commercial PE separator used is from Anhui Meixin New Materials Co., Ltd., with a thickness of 9+1+3+1 μm.
[0091] Structural characterization The thickness, pore size, porosity, and air permeability of the diaphragms obtained in Examples 1-7 and Comparative Examples 1-5 were tested, and the results are listed in Table 1.
[0092] Table 1 Physical properties of the diaphragms obtained in Examples 1-7 and Comparative Examples 1-5
[0093] Performance testing (1) The intrinsic viscosity, moisture content, glass transition temperature and rotational viscosity of the casting solution of the diaphragms obtained in the examples and comparative examples were tested, and the results are listed in Table 2.
[0094] Table 2 Comparison of diaphragm performance parameters between the examples and comparative examples
[0095] As shown in Table 2, compared with the aramid separator without fluorinated side chain modification (Comparative Example 1), the water content of the low-water-absorption aramid lithium battery separator prepared by the fluorinated side chain aramid polymer is easier to remove (Examples 1-7). Under the same drying conditions, its water content is close to that of the commercial PE separator (Comparative Examples 3-5). In the modified fluorinated side chain aramid separator, as the fluorinated aliphatic side chain lengthens, the fluorine content increases and the water absorption decreases.
[0096] (2) Electrical performance test The separators obtained in Example 5 and Comparative Examples 1-3 were assembled into lithium-ion batteries, wherein the positive electrode included a ternary positive electrode material (LiMn). 0.1 Co 0.1 Ni 0.8 The negative electrode comprises graphite, conductive carbon black, styrene-butadiene rubber, and binder (CMC) in a mass ratio of 97:2:1. The electrolyte solvent consists of DMC, EC, and DEC in a volume ratio of 1:1:1. The electrolyte is LiPF6 lithium salt with a concentration of 1 mol / L. In battery fabrication, the negative electrode, separator, and positive electrode are stacked sequentially, using the aforementioned electrolyte, along with commonly used tabs and aluminum-plastic film sealing materials. The nominal capacity is 13 Ah, and the operating voltage range is 2.6~4.2V.
[0097] The electrical performance of the above-mentioned batteries was tested, and the results are as follows: Figure 1 As shown. By Figure 1As can be seen, the aramid membranes modified with fluorinated side chains (Examples 1 and 5) exhibited cycling capacity retention rates comparable to those of commercial membranes (Comparative Example 3). Example 1 showed a capacity retention rate ≤80% after 798 cycles; Example 5 showed a capacity retention rate ≤80% after 855 cycles; the aramid membrane without fluorinated side chain modification (Comparative Example 1) showed a capacity retention rate ≤80% after 333 cycles; and Comparative Example 2, also modified with fluorinated side chain biphenyl diamine, showed a capacity retention rate ≤80% after 545 cycles. This is because Comparative Example 2 had a higher water content. Table 1 also shows that the aramid polymer in Example 5 exhibited 40%–50% lower water absorption than the aramid polymer in Comparative Example 2.
[0098] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A low-water-absorption aramid lithium battery separator, characterized in that, The film-forming raw material includes a fluorinated side-chain aramid polymer, which is obtained by polycondensation reaction of a fluorinated side-chain aromatic diamine and an aromatic dicarboxylic acid chloride. The fluorinated side-chain aromatic diamine has the structure shown in Formula 1 or Formula 2: Formula 1; Formula 2; In Equation 1, R is -OCH2(CF2). n X, n=3~10, X is F or H; In Equation 2, R f -O(CF2) m Y or -OCF2CFHOC3F7; the -O(CF2) m In Y, m = 1~4, and Y is F or H.
2. The low-water-absorption aramid lithium battery separator according to claim 1, characterized in that, A method for preparing a fluorinated aromatic diamine with the structure shown in Formula 1 includes the following steps: Under the action of triethylamine, a fluorinated alcohol having the structure shown in formula a undergoes an etherification reaction with 2,4-dinitrofluorobenzene to obtain a fluorinated dinitro compound having the structure shown in formula b. Formula a; Formula b; Under the action of a reducing agent, a fluorinated dinitro compound having the structure shown in Formula b undergoes a reduction reaction to obtain a fluorinated aromatic diamine with the structure shown in Formula 1.
3. The low-water-absorption aramid lithium battery separator according to claim 1, characterized in that, A method for preparing a fluorinated aromatic diamine with the structure shown in Formula 2 includes the following steps: Under the action of a reducing agent, 3-(fluoroalkoxy)nitrobenzene with the structure shown in formula c undergoes a reduction reaction to obtain a hydrazine derivative with the structure shown in formula d. Formula c; Formula d; Under the action of stannous chloride, hydrazine derivatives with the structure shown in formula d undergo acid-catalyzed rearrangement to obtain fluorinated aromatic diamines with the structure shown in formula 2.
4. The low-water-absorption aramid lithium battery separator according to claim 1, 2, or 3, characterized in that, The aromatic dicarboxylic chloride is isophthaloyl chloride and / or terephthaloyl chloride; The molar ratio of the fluorinated side-chain aromatic diamine to the aromatic dicarboxylic acid chloride is 1:(1~1.05). The intrinsic viscosity of the fluorinated side-chain aramid polymer is 1.6~3.5 dL / g.
5. The low-water-absorption aramid lithium battery separator according to claim 4, characterized in that, The fluorinated side-chain aramid polymer has the structure shown in Formula 3 or Formula 4: Formula 3; Equation 4; In equations 3 and 4, Z is or ; n=200~400。 6. The method for preparing the low-water-absorption aramid lithium battery separator according to any one of claims 1 to 5, characterized in that, Includes the following steps: A fluorinated side-chain aromatic diamine and aromatic dicarboxylic acid chloride are mixed with an organic solvent to carry out a polycondensation reaction. A neutralizing agent is added to the resulting polycondensation reaction solution to obtain a fluorinated side-chain aramid polymer slurry. The fluorinated side-chain aramid polymer slurry is mixed with a pore-forming agent to obtain a casting solution; The casting liquid is extruded onto the substrate surface to form a liquid film. The liquid film is then subjected to coagulation bath film formation, stretching, solvent removal, drying, and heat setting in sequence to obtain a low water absorption aramid lithium battery separator.
7. The preparation method according to claim 6, characterized in that, The neutralizing agent includes one or more of calcium hydroxide, potassium hydroxide, and sodium hydroxide; The solid content of the fluorinated side-chain aramid polymer slurry is 10-30%; The pore-forming agent includes one or more of calcium chloride, lithium chloride, polyvinylpyrrolidone, and polyethylene glycol; The mass of the pore-forming agent is 2-10% of the mass of the fluorinated side-chain aramid polymer slurry; The rotational viscosity of the casting solution is 150~900 Pa·s.
8. The preparation method according to claim 6, characterized in that, The coagulation bath comprises a first component and a second component; The first component includes water, or a combination of water and an alcohol solvent; The second component includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and triethyl phosphate; The mass ratio of the first component to the second component in the coagulation bath is (20~45):(55~80); The film-forming temperature in the coagulation bath is 10~40℃, and the time is 30~250s.
9. The application of the low water absorption aramid lithium battery separator according to any one of claims 1 to 5 or the low water absorption aramid lithium battery separator prepared by the preparation method according to any one of claims 6 to 8 in lithium-ion batteries.
10. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the separator is the low water absorption aramid lithium battery separator according to any one of claims 1 to 5 or the low water absorption aramid lithium battery separator prepared by the preparation method according to any one of claims 6 to 8.
Citation Information
Cited By
Modified aramid copolymer and preparation method thereof, copolymerized aramid diaphragm and preparation method thereof, and lithium ion battery
CN121673556A
